Outcome of Laparoscopic Total Extra Peritoneal Versus Lichtenstein Repair For Treatment of Inguinal Hernia: A Randomized Control Trial - Ahmad Raza Noumani; Ahmad Ammar; Muhammad Usman Aslam; Syed Asghar Naqi (Gandhara University, 2021)
OBJECTIVES: To compare the outcome of laparoscopic total extra peritoneal (TEP) repair versus Lichtenstein repair (LR) of inguinal hernia in terms of post-operative pain, hematoma, seroma, wound infection and early recurrence. METHODOLOGY: This randomized control trial was conducted at Surgical Unit III, General Hospital Lahore, Pakistan during the period June 2017 to May 2018. Male patients aged up to 50 years diagnosed with unilateral, reducible primary inguinal hernia were randomized into two groups, Group A (TEP) and Group B (LR), with 38 patients each. Data was collected prospectively on structured proforma. Patients were regularly followed up for one year for early postoperative complications. Statistical analysis was done using SPSS version 26. RESULTS: Out of 76 patients, mean age for TEP was 36.72±4.50 years and LR was 34.42±6.8 years. No significant difference was found in both the groups in terms of short-term postoperative complications. LR group had comparatively high rate of postoperative complications; hematoma formation (n=3/38; 7.9%), wound infection (n=3/38; 7.9%) and seroma formation (n=1/38; 2.6%). Postoperative pain with Visual Analogue Score in TEP group on the 1st day, 3rd day, 7th day and 1 month follow up was less as compared to LR group. CONCLUSION: The present study concludes that TEP is better than LR in inguinal hernia in terms of less postoperative pain after 1 month. However, no statistical difference was found in seroma and hematoma formation and wound infection.